EVALUATING THE EFFECTIVENESS OF CUSTOMER COMPLAINT RESPONSES ON NMB MKONONI SATISFACTION: A CASE STUDY OF NMB BANK PLC IN DODOMA CITY, TANZANIA - Mohamed Salum KILINDO; Nasibu Rajabu MRAMBA (Management & Marketing)
This research examines the efficiency of customer complaint responses and their impact on satisfaction with NMB Mkononi services in Tanzania, specifically focusing on NMB Bank PLC in Dodoma City. The study aims to evaluate how effectively NMB handles customer complaints related to NMB Mkononi services. A sample of 124 respondents, including NMB Mkononi customers, staff, and branch managers, participated in the study. Data were gathered through questionnaires, interviews, and document reviews, and analyzed using both qualitative and quantitative methods. Findings indicated moderate usage of NMB Mkononi services in Dodoma City and effective responses to customer complaints by NMB Bank (total mean = 3.56). The study concludes that NMB must consistently deliver high-quality services to customers and recommends enhanced investment in reliable network infrastructure, ICT expertise, facilities, and